Pathogenesis of cutaneous small-vessel vasculitis (CSVV) - Szczerkowska-Dobosz, Aneta; Roszkiewicz, Jadwiga; Lange, Magdalena; Jasiel-Walikowska, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
The term cutaneous small-vessel vasculitis (CSVV) includes heterogenous diseases characterized by different cutaneous haemorrhagic lesions and a different grade of systemic manifestations. Etiologic factors involve infections, drugs, chemicals, food allergens, chronic diseases and malignant neolasms. No cause is identified in more than 50% of patients. Pathogenesis of CSVV is connected with immune complexes, which under some circumstances may precipitate in tissues, causing typical for CSVV leukocytoclastic vasculitis. Lymphomonocytic infiltration due to secondary cell mediated immune response is characteristic for the late phase of the disease. Other immunological mechanisms involved in vasculitis pathogenesis include endothelial, cytokines, neurotransmiters and fibrynolysis disturbances. Recent studies have indicated g/d T lymphocytes and heat shock proteins to be involved in pathogenesis of CSVV with infective etiology. This article reviews the up-to-date data on pathogenesis of CSVV.